Efficacy of thermotherapy to treat cutaneous leishmaniasis : a meta-analysis of controlled clinical trials (2015)
ABSTRACT: Introduction: The efficacy of thermotherapy for the treatment of cutaneous leishmaniasis presents diverse results with low statistical power. Objective: To evaluate the efficacy of thermotherapy to treat cutaneous leishmaniasis. Methods: A meta-analysis of controlled clinical trials in 12 databases based on the implementation of a research protocol with inclusion and exclusion criteria and an assessment of methodological quality. The reproducibility and completeness were guaranteed in the information search and extraction. Heterogeneity, sensitivity and publication bias were assessed by graphical methods (Galbraith, L'Abblé, funnel plot, Egger plot, and influence plot) and analytical methods (DerSimonian-Laird, Begg and Egger). Random-effects forest plots were constructed, and a cumulative meta-analysis was performed. Results: Eight studies were included with 622 patients who underwent thermotherapy, with an efficacy of 73.2% (95% confidence interval (CI) = 69.6-76.7%), and with 667 patients who underwent systemic treatment, with an efficacy of 70.6% (95% CI=67.1-74.1%). Heterogeneity between studies, good sensitivity for the combined measure, and no publication bias were observed. The relative risk for comparison of the efficacy of treatment was 1.02 (95% CI=0.91, 1.15), showing that the effectiveness of thermotherapy is equal to that of pentavalent antimonial drugs. Conclusión: Due to its efficacy, greater safety and lower cost, thermotherapy should be the first treatment option for cutaneous leishmaniasis in areas where the prevalence of the mucocutaneous form is low and in patients with contraindications to systemic treatment, such as kidney, liver and heart diseases, as well as in pregnant women, infants, and patients with human immunodeficiency virus infection/acquired immune deficiency syndrome.